-2(4x-1)=-4-8x

Simple and best practice solution for -2(4x-1)=-4-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x-1)=-4-8x equation:


Simplifying
-2(4x + -1) = -4 + -8x

Reorder the terms:
-2(-1 + 4x) = -4 + -8x
(-1 * -2 + 4x * -2) = -4 + -8x
(2 + -8x) = -4 + -8x

Add '8x' to each side of the equation.
2 + -8x + 8x = -4 + -8x + 8x

Combine like terms: -8x + 8x = 0
2 + 0 = -4 + -8x + 8x
2 = -4 + -8x + 8x

Combine like terms: -8x + 8x = 0
2 = -4 + 0
2 = -4

Solving
2 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6x-6-5=-11+6x | | Log(5x+70)=3 | | 0.6x=0.4-0.2 | | 2+7(4-2x)=100 | | 2v^2-6v-56= | | -24=4r-r | | 6v-10v-15=15+11v | | 2.00+1.00*2=46.00 | | 2.8z=-92.4 | | 5y=3x^2-6 | | -6+4n=4n-6 | | Y=2(-5+y)+2 | | -14p+8=22-20p | | 4(2x-1)=21 | | 27c^2+108+108=0 | | 2(1-4x)-2x=3x | | 5-x/4=7 | | 2(1-4x)-2=3x | | -9j-8=-7-9j | | Y-2.7=22.1 | | 3(x-2)-x=-2+2x | | -2+2x=3(x+3) | | 2j-9=20t | | 9+w=-w-9 | | n^2-n-30= | | -14p+8=22+20p | | (8x+15)=90 | | Y-2.7=22-1 | | 40.55+0.25m=130 | | 3p-4=5p+12 | | (x+3)(x-5)-(4x+2)(x+4)= | | 6sqrt(x-2)-5=4 |

Equations solver categories